Characterization of isolates of Beauveria bassiana isolated from cofee-berry borer, Hypothenemus hampei - RIVERA-M., ARMANDO; BRIDGE, PAUL D.; BUSTILLO-P., ALEX E. (Revista Colombiana de Entomología, 1997)
Thirty six isolates of B. bassiana were studied, these comprised 16 from coffee berry borer (CBB) in Colombia and 20 from other regions of the world. The fungal biochemical activity was evaluated using vine extracellular enzymes involved in the degradation of complex material (e.g. proteins, chitin, and polysacharides). These were tested by degradation, incorporating particular substrates into modified agar growth media. The enzyme systems tested in this way were elastase, gelatinase, fatty acid degrading enzymes, and fatty acid utilization or testing the spent culture Huid with specific enzyme substrates that were substituted with methylumbelliferone (nacetylglucosaminidase, glucosidase, diacetylchitobiosidase, fucosidase, xylosidase and cellobiosidase). The relationship among the isolates was evaluated examining isoenzymes and individual proteins were separated by electrophoresis in discontinuous polyacrylamide gels. Gels were stained for catalase, acid, and alkaline phosphatase and esterase (acetate and propionate) activities. DNA was amplified using the polymerase chain reaction (PCR) with four different single primers based on simple sequences. All isolates showed glucosidase, n-acetylglucosaminidase, and elastase activity. No isolates displayed fucosidase activity and the different isolates showed differential results with the different physiological tests. The isolates could be split into two broad groups on the basis of these reactions, one group consisting predominantly of isolates with high protease and low chitinase activities, and one group consisting predominantly of isolates with low protease but good chitinase activity. Most isolates had very similar patterns of iso-enzyme and PCR bands although a few isolates gave unique patterns. Analysis of the major and minor pattern differences did non show any simple correlations with host, geographic origin, or pathogenicity. There is apparently little genetic variability among the isolates and most of them are very closely related.